Maximized performance of dye solar cells on plastic: a combined theoretical and experimental optimization approach. Issue 6 (21st April 2016) - Li, Yuelong; Carretero-Palacios, Sol; Yoo, Kicheon; Kim, Jong Hak; Jiménez-Solano, Alberto; Lee, Chul-Ho; Míguez, Hernán; Ko, Min Jae
Abstract : Maximizing the performance of dye solar cells on plastic using a combined theoretical and experimental optimization approach. Abstract : We demonstrate that a combined optimization approach based on the sequential alternation of theoretical analysis and experimental realization gives rise to plastic supported dye solar cells for which both light harvesting efficiency and electron collection are maximized. Rationalized configurations with optimized light trapping and charge extraction are realized to achieve photoanodes on plastic prepared at low temperature, showing a power conversion efficiency of 8.55% and a short circuit photocurrent of 16.11 mA cm −2, unprecedented for plastic based dye solar cell devices. Furthermore, the corresponding fully flexible designs present stable mechanical properties after several bending cycles, displaying 7.79% power conversion efficiency, an average broadband internal quantum efficiency above 90%, and a short circuit photocurrent of 15.94 mA cm −2, which is the largest reported value for bendable cells of this sort to date.